Teacher professional development: ''Be a force for good'' - Lilia Indriani; Dwitiya Ari Nugrahaeni; Noor Sahid Kusuma Hadi Manggolo; Panggih Rahardi (Journal of Community Service and Empowerment, 2023)
The teacher's lack of understanding of the use of technology in the classroom seems to be inversely proportional to the Merdeka Curriculum which requires teachers and students to be able to keep up with technological developments. Therefore, training on the use of the Canva application as a learning medium for elementary school teachers in Magelang was carried out as teacher professional development effort. The aim of this community service is to train elementary school teachers so they can develop their professionalism in developing interactive learning media that suits students' needs in the current era. By carrying out this community service in three different schools with a total of 22 participants, several stages were carried out. These stages consist of analyzing community problems, identifying problems, finding solutions to problems, preparing activities, implementing activities, evaluating activities and results. The evaluation results of this training activity showed that not only can the participants become more familiar with the Canva application, they are also trained to be able to design learning media in the form of presentations and videos using Canva. The participant satisfaction survey also showed positive results, in fact all participants agreed that they would continue to use Canva as a technology for designing learning media in the future. The root of this solution will certainly have an effect on the students' understanding of the participants later. If students have good academic achievements, they will become the next generation of the nation who can solve problems in this country, including poverty. However, this study was also conducted as a form of community service report which hopefully still can be a guideline and reading material for researchers regarding community service out there.